Sex‐Specific Differences in the Predictive Value of Cholesterol Homeostasis Markers and 10‐Year Cardiovascular Disease Event Rate in Framingham Offspring Study Participants. Issue 1 (19th February 2013) - Matthan, Nirupa R.; Zhu, Lei; Pencina, Michael; D'Agostino, Ralph B.; Schaefer, Ernst J.; Lichtenstein, Alice H.
Abstract : Background: Available data are inconsistent regarding factors influencing plasma cholesterol homeostasis marker concentrations and their value in predicting subsequent cardiovascular disease (CVD) events. Methods and Results: To address this issue, the relationship between markers of cholesterol absorption (campesterol, sitosterol, cholestanol) and synthesis (squalene, desmosterol, lathosterol) and 10‐year CVD incidence was assessed in Framingham Offspring Study participants (cycle 6) who were without CVD at baseline and not taking lipid‐lowering medications (N=2616). The primary end point was "hard" coronary heart disease (HCHD; coronary death and myocardial infarction), and the secondary end point was full CVD (HCHD plus stroke, coronary insufficiency, angina pectoris, peripheral artery disease, and congestive heart failure). In cross‐sectional analysis, significant differences by sex, age, body mass index, blood pressure, and smoking status were observed. In both women and men, lower cholesterol absorption was associated with higher triglyceride and lower high‐density lipoprotein (HDL) cholesterol concentrations, whereas lower cholesterol synthesis was associated with higher low‐density lipoprotein (LDL) cholesterol concentrations ( P for trend <0.05). In women only, lower cholesterol synthesis and absorption were associated with higher non–HDL cholesterol concentrations. Using Cox proportional hazards model adjusting for standard CVD risk factors, squalene concentrations were associated with lower HCHD in women (hazard ratio=0.70 [0.5 to 0.9]). In contrast, squalene (hazard ratio=1.40 [1.1 to 1.8]) concentrations were associated with higher HCHD in men ( P <0.0001 for interaction). The cholesterol absorption markers were not predictive of HCHD or full CVD in either women or men. Conclusions: These data suggest significant sex differences in the 10‐year prognostic value of cholesterol synthesis markers and HCHD, specifically coronary death and incidence of myocardial infarction. Clinical Trial Registration: URL:http://ClinicalTrials.gov . Unique identifier: NCT00074464.